Tessituras teórico-conceituais sobre Inovação: uma análise das pesquisas brasileiras no âmbito dos Programas de Pós-Graduação em Ciência da Informação - Carlucci, Renan Augusto (2023)
Innovation has been the subject of study across various domains of knowledge. Within the field of Information Science, there exists a diversity of approaches to the theme. Consequently, the question arises: how has innovation been conceptualized and addressed in the research published by Postgraduate Programs in Information Science in Brazil? To address this query, the study aimed to investigate scientific publications expressed through dissertations and theses defended in the field of Information Science within the Brazilian context. The objective was to map the scientific production on the topic of innovation within dissertations and theses defended in Brazilian Postgraduate Programs in Information Science, with the aim of identifying: a) the conceptualization of innovation in the conducted research; b) the approaches employed in addressing innovation; c) the bibliography utilized in constructing the conceptual framework; and d) networks of cited works. Characterized by a descriptive and exploratory methodology, the research adopted the Systematic Literature Mapping (SLM) method to support the discussion and develop a theoretical framework for the innovation theme within the Brazilian Information Science community. Seventy-two works were identified, comprising 47 master's dissertations and 25 doctoral theses that explicitly addressed the concept of innovation. The results presented encompassed the mapping of concepts and approaches used in the innovation domain, the authors who produced the academic-scientific works, the bibliography utilized to support the epistemological conception of the concept, and the network of cited works. In the realm of scientific research, innovation concepts manifest along 03 (three) central domains: epistemological, historical, and economic-industrial. It was concluded that Innovation is a topic of research agenda within Information Science, considering information and knowledge as foundational elements in the inventive process, which precedes the emergence of innovation. Notably, innovation is characterized as an applied invention, whose utility and scope present as a viable solution to a specific need within a given context.